2017
DOI: 10.3389/fnagi.2017.00404
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Increases in Benign Paroxysmal Positional Vertigo Are Reversed in Women Taking Estrogen Replacement Therapy: A Population-Based Study in Taiwan

Abstract: Benign paroxysmal positional vertigo (BPPV) is the most common cause of peripheral vertigo. Numerous investigations have reported an increased BPPV incidence in females and in the aged population. The hormonal characteristics of BPPV patients have not been previously investigated. This study aimed to determine the risk of BPPV in relation to menopause in a population-based study.Materials and Methods: This retrospective population-based study was designed to use a nationwide longitudinal health insurance datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 44 publications
3
27
1
1
Order By: Relevance
“…It accounts for 8% of dizziness/vertigo in the general population (von Brevern et al, 2007), 34% of dizziness in persons aged 50 years and older (Davis, 1994), and 39% of dizziness in persons 70 years and older (Katsarkas, 1994). The prevalence of BPPV increases with age such that it is seven times higher in those aged 65 years and over relative to those aged 15–40 years (Liu et al, 2017; von Brevern et al, 2007).…”
Section: Prevalence Of Vestibular Dysfunction In the Elderlymentioning
confidence: 99%
“…It accounts for 8% of dizziness/vertigo in the general population (von Brevern et al, 2007), 34% of dizziness in persons aged 50 years and older (Davis, 1994), and 39% of dizziness in persons 70 years and older (Katsarkas, 1994). The prevalence of BPPV increases with age such that it is seven times higher in those aged 65 years and over relative to those aged 15–40 years (Liu et al, 2017; von Brevern et al, 2007).…”
Section: Prevalence Of Vestibular Dysfunction In the Elderlymentioning
confidence: 99%
“…Similarly, in the present study, there is a predominance of female sex, accounting for about 67.2% of BPPV patients. This female preponderance may be linked to hormonal factors (25). Estrogen deficiency has been shown to disturb the internal structure of the otoconia and their interconnection and attachment to the matrix (26).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in estrogen levels may lead to systemic disturbances in calcium metabolism and affect the synthesis and function of otoliths (13). Studies have found that the incidence of BPPV in women receiving hormone replacement therapy for menopausal symptoms was significantly reduced (14). Bárány Society's diagnostic criteria for BPPV is a diagnostic guideline jointly created by vestibular specialists from many countries.…”
Section: Discussionmentioning
confidence: 99%